Student Satisfaction in Learning Services: A Systematic Review of Scopus Data-Based Based on the PRISMA Approach (2015-2025) - Kalimah Thoyyibah; Sugiarto Sugiarto; Muh Takdir; Kamaludin Kamaludin (FKIP - Universitas Riau, 2026)
This study aims to identify and analyze the factors affecting student satisfaction with learning services during the period 2015-2025. This study used a Systematic Literature Review (SLR) approach, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 400 articles were identified from Scopus. After the selection, screening, and feasibility evaluation, 27 articles met the inclusion criteria for in-depth analysis. The analysis was carried out on four main focuses, namely: (1) concepts related to student satisfaction, (2) research trends regarding student satisfaction, (3) factors that affect student satisfaction, and (4) the influence of educator-student interaction on satisfaction levels. The study found that student satisfaction was influenced by the quality of teaching, the relevance of the material, learning motivation, and interpersonal support from educators. In addition, the development of online learning technology and student involvement in the learning process have proven to be key factors in increasing satisfaction. These findings make an important contribution to the development of learning service policies and practices that are more student-oriented and adapt to the dynamics of the digital era.